Critical evaluation of physical activity questionnaires translated to Brazilian-Portuguese: a systematic review on cross-cultural adaptation and measurements properties - Silva, Fernanda Gonçalves [UNESP]; Oliveira, Crystian Bitencourt [UNESP]; Hisamatsu, Thalysi Mayumi [UNESP]; Negrão Filho, Ruben Faria [UNESP]; Rodrigues, Caio Russo Dutra [UNESP]; Franco, Marcia Rodrigues; Pinto, Rafael Zambelli (Elsevier, 2019)
Background: The number of questionnaires that measures physical activity levels has increased considerably. For Brazilian population it becomes a challenge, due to the need of a rigorous translation, adaptation and testing of measurement properties. Objective: Evaluate the methodological quality and criteria of physical activity questionnaires translated to Brazilian-Portuguese. Methods: Methodological quality and quality criteria was assessed using the COnsensus-based Standards for the selection of health Measurement INstruments checklist. Results: Sixty-nine studies were included, the most frequent questionnaires investigated were the International Physical Activity Questionnaire (n = 16)and the Baecke Physical Activity Questionnaire (n = 12). Translation (n = 13), reliability (n = 37)and construct validity (n = 44)were the measurement properties commonly investigated. For reliability, most studies were rated as ‘adequate’ for methodological quality. The Intraclass Correlation Coefficient of the questionnaires ranged from 0.20 to 1.0. For construct validity, 31 analyses showed ‘inadequate’ methodological quality, due to poor description of the comparator instrument. High level of evidence on reliability were found for Baecke Physical Activity Questionnaire, Self-administered Physical Activity Checklist and Physical Activity Questionnaire of the Surveillance System of Risk Factors and Protection for Chronic Diseases; on construct validity for Self-administered Physical Activity Checklist, Physical activity Questionnaire for Adolescents, Physical activity Questionnaire for Older Children and Saúde naBoa Questionnaire. Conclusion: Most questionnaires showed poor methodological quality and measurement properties. The Baecke Physical Activity Questionnaire and Self-administred Physical Activity Checklist showed better scorings for methodological quality and quality criteria. Further high methodological quality studies are still warranted.
Keywords: Physical activity; Physical therapy; Psychometric properties; Questionnaire; Reliability; Validation